Lifestyle differences between co-twins are associated with decreased similarity in their internal and external exposome profiles - Drouard, Gabin; Wang, Zhiyang; Heikkinen, Aino; Foraster, Maria; Julvez, Jordi; Kanninen, Katja M.; van Kamp, Irene; Pirinen, Matti; Ollikainen, Miina; Kaprio, Jaakko (Scientific reports, 2024)
Whether differences in lifestyle between co-twins are reflected in differences in their internal or external exposome profiles remains largely underexplored. We therefore investigated whether within-pair differences in lifestyle were associated with within-pair differences in exposome profiles across four domains: the external exposome, proteome, metabolome and epigenetic age acceleration (EAA). For each domain, we assessed the similarity of co-twin profiles using Gaussian similarities in up to 257 young adult same-sex twin pairs (54% monozygotic). We additionally tested whether similarity in one domain translated into greater similarity in another. Results suggest that a lower degree of similarity in co-twins' exposome profiles was associated with greater differences in their behavior and substance use. The strongest association was identified between excessive drinking behavior and the external exposome. Overall, our study demonstrates how social behavior and especially substance use are connected to the internal and external exposomes, while controlling for familial confounders.